Design and development of multiband multi-mode frequency reconfigurable CPW-fed antenna for 5G wireless communication - Tiwari, Annu; Yilmaz, Muhammed Yasir; Soni, Gaurav Kumar; Yadav, Dinesh (Institute of Advanced Engineering and Science, 2025)
This research develops, simulates, fabricates and measured a coplanar waveguide (CPW)-fed multiband multi-mode frequency reconfigurable antenna for 5G wireless communication. The antenna is design on Rogers RT5880 substrate with a dielectric constant of 2.2, a thickness of 0.508 mm, and a loss tangent (tanδ) of 0.0009 and the dimension is 30×28×0.508 mm3. The presented antenna has shown good impedance matching with reflection coefficients ranging from -14.82 to -50.36 dB at different frequencies between 6 GHz to 24 GHz. The presented frequency reconfigurable antenna design includes four PIN diodes, resistors, and inductors, enabling 16 different configurations. The simulated outcomes showed varied S parameter values and gains, demonstrating the antenna's flexibility. Measurements were taken using vector network analyzer (VNA) and anechoic chamber to assess reflection coefficient (|S11|) and gain, confirming the antenna's performance. The antenna's ability to reconfigure dynamically without losing signal integrity makes it suitable for 5G wireless applications. It meets and exceeds the requirements for multiband operation, validated by comprehensive simulations and measurements, showing its potential for wide use.